Downsizing: Case of Intellectual Capital Performance Anorexia or Enhancement? - Williams, S. Mitchell (Institutional Knowledge at Singapore Management University, 2004)
The objective of this paper is to investigate if downsizing contributes to, or impedes, a firm's intellectual capital performance (ICE) based on a longitudinal analysis of 56 United States publicly listed companies that significantly downsized their workforce during the mid-1990s. Empirical analysis indicates that for the majority of firms, ICE consistently declined annually for the first 3 years, following downsizing with a moderate increase in the fourth year. Findings provide several interesting insights and conclusions. Most importantly, downsizing appears to have a negative impact on a firm's ICE following the reduction in workforce number. The impact of downsizing appears to be more significant amongst IC resource rather than traditional (physical capital) based firms. It is recommended that corporate directors and managers seek alternative strategies to address poor performance and competitive results than immediately downsizing their workforce as such action affects ICE.